HAND-ARM VIBRATION IN DIFFERENT OPERATING CONDITIONS WITH A CHAINSAW - Depoi, Juliano dos Santos; Brandelero, Catize; Werner, Valmir; Schlosser, José Fernando; Russini, Alexandre; de Vargas, Francieli (Floresta, 2022)
The mechanization of forest harvesting is a trend in Brazil. However, small and medium-sized companies in the forestry sector, even today, opt for semi-mechanized harvesting, using chainsaws for the harvesting and sectioning of trees. Despite technological advances, when operated continuously, chainsaws may cause damage to the operator’s body, acting as a stressor, and vibration excess is responsible for numerous health disorders, among them the Raynaud syndrome. In this sense, this study aimed to determine the vibration levels to which a chainsaw operator is subjected, during the transversal cut (tracing) of the wood, in different forest species and cutting sets. The treatments consisted of three forest species (Eucalyptus grandis, Eucalyptus dunnii and Acacia mearnsii De Wild) and two cutting sets, consisting of square tooth chains of the semi-chisel and chisel types. The vibration assessment was based on the criteria established by the Regulatory Standards NR15, NHO10 and ISO 2631-4. The results of vibration levels were higher than the reference limits established by ISO 2631-4, and, for both cutting sets, the highest vibration levels occurred on the “x” axis. After the data processing, the acceleration values resulting from the normalized exposure to hand-arm vibrations showed significant differences for the “y” and “z” axes. Therefore, it can be inferred that the chainsaw operation is a stressor, potentially capable of causing damage to workers' health.